The difficulties of physical education in remote classes: the reality in state indigenous schools in Rio Tinto/PB (Research, Society and Development, 2022)
Indigenous school education, too, can and/or should describe its adversities passed through in the remote teaching scenario, essentially, the professionals of the physical education curricular component. The objective of this article is to identify the behaviors, mechanisms and dissolutions of school physical education teachers, reflecting on the possible difficulties, to teach remote classes, in the indigenous schools of Rio Tinto. The essay approach, supported by a select literature review, working with a closed questionnaire for data collection, through google forms, is implemented as its methodology. The data collected demonstrate, without hesitation, the difficulties present in the indigenous schools of Rio Tinto during the period of remote teaching. Although we currently understand and try to measure the negative impacts of the pandemic on school education, we still lack this overview for realities where the specifics must be seen from a plural perspective. Therefore, this discussion shows that we will be, yes, in the tireless and incessant search to create opportunities for a dignified and quality indigenous school education, with equity, even in remote classes.